Preductal Segmental Tubular Aortic Hypoplasia in Perinatally Died Stabyhoun Puppies - Marie D. B. van Staveren; Guy C. M. Grinwis; Marjolein L. den Toom; Viktor Szatmári (Animals, 2023)
Background: A high perinatal mortality rate in the Stabyhoun breed prompted one of the Dutch breeding organizations to start an investigation. Preductal segmental tubular aortic hypoplasia is an extremely rarely documented congenital vascular anomaly in dogs, and it is suspected to be the result of constriction of ectopic ductal tissue in the aortic wall at birth. Methods: Over a period of 18 months, Stabyhoun puppies that were stillborn, died or were euthanized before 3 weeks of age were submitted to post-mortem examination at the reporting institution. Pathologic findings were documented. Results: Eight Stabyhoun puppies were submitted during the study period. In five of them, a severe preductal segmental tubular aortic hypoplasia was found. Two of the five puppies were stillborn, and three died spontaneously or were euthanized. Conclusions: Preductal tubular aortic hypoplasia was found in an unusually high frequency in the examined Stabyhoun puppies. Because the condition is believed to cause clinical signs only after birth, this anomaly cannot explain the death of the stillborn puppies. However, it might be responsible for cardiogenic pulmonary edema in the postnatal period. Routine dissection of the great vessels in perinatally deceased puppies would help to establish the prevalence of congenital anomalies of the aorta.